POSITIVE TEACHER-STUDENT RELATIONSHIPS FOR EFFECTIVE LEARNING - Siburian, Naomi Sonya Fitri; Indriani, Siane (Universitas Pelita Harapan, 2024)
The distance between teacher and students can affect students’ performance in the teaching and learning process. On the other hand, a Christian teacher as an agent of reconciliation should build a positive relationship with the students by showing love and caring as God does it first to us. Thus, this paper aims to know the importance and the possible ways of creating a positive teacher-student relationship for effective learning. Through the literature review, the writer found that a positive teacher-student relationship has impacted students’ performance, by which they will be more confident and motivated to participate in the learning process. Hence, the teacher must be flexible and be able to select the most suitable ways to build a positive relationship. It is recommended for the next researcher to find ways to embed the boundaries amid positive relationships. Bahasa Indonesia AbstrakJarak antara guru dengan siswa dapat mempengaruhi prestasi siswa dalam proses belajar mengajar. Di sisi lain, seorang guru Kristen sebagai agen rekonsiliasi harus membangun hubungan guru-siswa yang positif melalui tindakan kasih dan kepedulian seperti yang telah Allah lakukan lebih dahulu. Oleh karena itu, makalah ini bertujuan untuk mengetahui pentingnya dan cara-cara yang memungkinkan untuk menciptakan relasi guru-siswa yang positif. Melalui kajian literatur, penulis menemukan bahwa relasi ini memberikan dampak bagi prestasi siwa, dimana mereka lebih percaya diri dan termotivasi untuk berpartisipasi dalam proses pembelajaran. Maka, guru Kristen harus mampu untuk menjadi fleksibel dan mampu untuk memilih mana cara yang paling tepat dan cara yang harus dihindari dalam membangun relasi guru-siswa yang positif. Disarankan kepada peneliti selanjutnya untuk menemukan bagaimana cara menanamkan batasan di tengah-tengah relasi yang positif.